KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI PADA SISWA KELAS X SMA NEGERI 8 KOTA KUPANG - Morgan Ibrahim Filmon Seseli; Samuel H. Nitbani; Dian Sari Pekuwali (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The focus of this research is “How is the Ability to Write Observation Report Texts among Tenth-Grade Students of SMA Negeri 8 Kupang City?” This study aims to describe the competence of tenth-grade students at SMA Negeri 8 Kupang City in writing observation report texts. The study is based on the theoretical foundation of writing skills, specifically focused on the construction of observation report texts as the primary measurement instrument. By applying a qualitative descriptive methodology, the researcher analyzed students’ mastery of observation report texts, which are a type of text presenting factual, systematic, and objective data obtained through direct observation. The empirical findings from the data analysis of 25 respondents indicate that the students’ ability to compose such texts, while considering structural aspects and applicable linguistic features, has reached the competent category. This is evidenced by the results showing that 17 students, or 68%, achieved mastery learning by meeting the minimum passing criterion (KKM) of 75 or above, while 8 students, or 32%, did not achieve mastery learning or failed to meet the KKM.